Understanding the profitability gap between euro area and US global systemically important banks - Luca Di Vito; Natalia Fuentes; Joao Matos Leite (European Central Bank (ECB), 2023)
This investigation starts with the observation that, over the last decade, profitability rates reported by euro area (EA) banks have remained, on average, persistently below those reported by peer banks in the United States (US). In particular, banks' return on equity (ROE) has fluctuated around 5% in the EA, but around 10% in the US, indicating a profitability gap of around 5 percentage points.1 However, while comparisons are frequently made between EA and US banks in academic and political debate, they are not perfect benchmarks, nor should this paper be regarded as aiming for a like-for-like comparison. This paper seeks to identify and analyse the factors behind the profitability gap in a structured manner. We disaggregate the gap between EA and US global systemically important banks (G-SIBs) into the different contributing items in the profit and loss (P&L) statement and then take a deep dive into the drivers for 2021. Our analysis highlights two main drivers of US G-SIBs' higher profitability. First, the higher income from fees and commissions and trading of US G-SIBs explains the bulk of the difference in ROE. Second, EA G-SIBs are still dealing with legacy nonperforming exposures built up during the Global Financial Crisis (GFC) which have driven up the associated impairments and provisions expenses beyond that of US peers. While we do not aim to provide normative recommendations in this paper, our main conclusion is that the higher profitability of US G-SIBs compared with their EA peers can largely be explained by their different business strategies, which are closely linked to the differing macroeconomic environments and financial systems in which these banks operate. Furthermore, this analysis does not provide a comprehensive picture of US and EA G-SIBs' performance: with the focus on profitability, other important aspects related to risk taking, business model sustainability, and prudential regulation are not included. Regulatory differences across banking systems are not addressed in this investigation.
Keywords: G15; G21; 330; Bank profitability; global systemically important (G-SIB) banks; return onequity